Bioethanol Production from Brewer’s Spent Grain through simultaneous saccharification and Fermentation process - Melese Nigusu (ASTU, 2025)
Increasing bioethanol production from biomass fermentation has gained worldwide attention to reduce fossil fuel depletion, rising oil prices, and environmental impacts. This study investigates production of bioethanol from Brewery Spent Grain using simultaneous Saccharification and fermentation process (SSF)”.for the Produce of bioethanol from brewery spent grain using different methods for this research the BSG sample was pretreatment using torrifaction process at different temperature and time. After the torrifaction process the three components (cellulose, hemicellulose and lignin) was determine. Than the treated BSG sample was first stage NaOH followed by acid (H2SO4) hydrolysis pre-treatment was done. The selected torified sample was at temperatures of 1200c and 2200c for 30 minute and 60 minute for comparisons purpose. The 4% NaOH used to for lignin and hemicellulose removal, structural disruption and enhanced fermentable sugars and the acid was used to for hemicellulose hydrolysis, enhanced cellulose access and increased glucose yield. The second stage hydrolysis process using SSF. In this step both saccharification and fermentation process was done simultaneous using shaker incubator for three days the sample to yeast ratio was 5:1 and the sample to acid ratio was 1:10. Yeast was used to facilitate for the fermentation process and the acid was used to for hydrolysis conversion of cellulose in to glucose. The amount of glucose was calculated in to 24, 48 and 72h using glucose standard. Finally the distillation process was done and volume of the bioethanol was measured. The volume of the sample BSG approximately 0.9 mL/g or Percentage yield 90% .And there was a lot of characterization technics were take place. Those are FTIR, oxidation test, combustion of bioethanol and density determination. This work illustrated that BSG could be converted into bioethanol efficiently by pretreatment of torrefaction, chemical hydrolysis and SSF. Of the conditions tested, 120 °C torrefaction gave greater ethanol yields than 220 °C and achieved an ultimate yield of ~0.9 mL/g or 90%. These findings demonstrate that the bioethanol production could be significantly improved by optimizing the pretreatment and fermentation conditions, and it is a prospective way to convert of industrial wastes into value-added products such as bioenergy.